Kajian Literatur: Pengaruh Penambahan Hati Ayam terhadap Kandungan Zat Besi pada Produk Formulasi Makanan untuk Mencegah Anemia - Hafizotun Tsaqifah; Tasya Shafa Salsabila Muda; Dhiyah Ariba Oktaviani; Annis Catur Adi (Media Gizi Kesmas, 2024)
Backgound: Iron (Fe) together with protein is needed by the body in the formation of hemoglobin so that if the amount of intake is less, the number of red blood cells used to transport oxygen to the lungs is not enough to meet the physiological needs of the body with normal hemoglobin levels of 12-15 g/dl in female adolescents and 13-17 g/dl in male adolescents. Iron deficiency causes disturbances or obstacles to growth which can cause symptoms of lethargy, weakness, fatigue and forgetfulness to anemia. Chicken liver is the most common source of iron used as a food formulation additive because it is easily accessible and is a source of heme iron which is more easily absorbed and contains less mineral binding material. Therefore, nutrient fortification in food formulations by utilizing chicken liver is needed to prevent anemia. Objectives: The effect of iron nutrient levels from the results of food formulations was analyzed by utilizing chicken liver as a substitute material intended to increase iron intake in an effort to prevent anemia. Methods: This research used the Literature Review method by tracing and reviewing several similar research articles that used experimental studies, especially in terms of product development that utilized chicken liver as a source of iron intake. The article search used the Google Scholar electronic database within the last 10 years (2014-2024) with keywords “anemia”, "iron", "food formulations", and "chicken liver". Results: From the 12 articles found, all formulas met the percentage of daily iron requirements according to the targets set by each study. The best formula had the highest iron content, which was 14.05 mg per 100 grams, while the formulation with the lowest iron content still met the target percentage of Recommended Dietary Allowance (RDA), which was 2.04 mg per 100 grams. The difference in iron content among the studies could be influenced by the percentage of chicken liver added to the formulation and the addition of other potential food ingredients. Conclusions: There is an effect of iron levels produced by food formulation products with the addition of chicken liver which has the potential to prevent anemia in the community.